Legal Framework for Environmental Economic Instruments to Reduce Greenhouse Gas Emissions - A. Melantik Rompegading; Sri Handayani (Postgraduate, University of Mataram, 2023)
Abstract: Environmental damage due to greenhouse gas emissions affects forest sustainability in Bantimurung National Park, Maros. It takes the participation of all parties to overcome this. The purpose of this research is to analyze the legal framework for environmental economic instruments to reduce greenhouse gas emissions in Bantumutung National Park, Maros. This research method uses explanatory data using secondary data from Law Number 32 of 2009 concerning the Protection and Preservation of the Environment from the Ministry of Forestry and Environment; PP No. 46 of 2017 concerning Environmental Economic Instruments from the Ministry of Environment and Forestry; and Regional Regulation of the Maros Regency Government No 05 of 2009. The Maros district government has played an active role in efforts to reduce greenhouse emissions. This can be seen by funding the P4JH program through the APBD. To maximize environmental economic instruments in forest management, it is recommended to apply for funding not only from the regional budget but also from ICCTF grants. At the provincial level of South Sulawesi, it is necessary to draw up a Governor's regulation that regulates the tagging and scoring budget as a strengthening of the government's role. At the district level, it is recommended to renew the Regional Regulation which regulates the technical implementation of tree planting by civil servants starting from the selection of land locations, types of plants, and the mechanism as a condition for promotion or other matters.